2016
DOI: 10.5505/tjtes.2016.72662
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Ottawa ankle rules by general practitioners in an emergency department of a Turkish district hospital

Abstract: BACKGROUND:The present objective was to assess implementation of the Ottawa ankle rules (OAR) as a method of fracture prediction in the emergency department (ED) of a Turkish state hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Referrals for imaging were excluded from the study if participants were under 18 years of age, returning for follow-up imaging, presenting with a multi-trauma, had an injury more than two weeks old, had cognitive impairment (including intoxication), had an incomplete examination, had an inflammatory, neurological or musculoskeletal condition that impeded ankle joint function, the referral gave no fracture subscription (i.e., query foreign body, prosthesis position), or requested imaging for a known dislocation or post-reduction of a dislocation. This is consistent with previous literature ( Daþ, Temiz & Çevik, 2016 , p. 362; Pijnenburg et al, 2002 , p. 601).…”
Section: Methodssupporting
confidence: 94%
See 1 more Smart Citation
“…Referrals for imaging were excluded from the study if participants were under 18 years of age, returning for follow-up imaging, presenting with a multi-trauma, had an injury more than two weeks old, had cognitive impairment (including intoxication), had an incomplete examination, had an inflammatory, neurological or musculoskeletal condition that impeded ankle joint function, the referral gave no fracture subscription (i.e., query foreign body, prosthesis position), or requested imaging for a known dislocation or post-reduction of a dislocation. This is consistent with previous literature ( Daþ, Temiz & Çevik, 2016 , p. 362; Pijnenburg et al, 2002 , p. 601).…”
Section: Methodssupporting
confidence: 94%
“…The OAR have been widely applied in many countries ( Daþ, Temiz & Çevik, 2016 ) and there have been active dissemination and education strategies developed to encourage clinicians to incorporate them into practice ( Cameron & Naylor, 1999 ). However, Cameron & Naylor (1999) report that OAR have not been universally adopted into practice, potentially due to the convenience of referring patients with ankle trauma for imaging, or due to practitioners’ concerns around litigation ( Pires et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…By minimizing unnecessary radiography, this clinical tool streamlines the diagnostic process and facilitates more efficient use of emergency department resources. [13,14] However, the limitations of the OAR must be recognized. Specifically, given the risk of overlooking certain fracture types, a holistic approach that incorporates clinical evaluation and patient history is essential.…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40] This would suggest a risk of a patient failing to receive baseline imaging if evidence-based guidelines for imaging are followed. Because the Ottawa Ankle Rules do not always achieve 100% sensitivity, [41][42][43] it may be of value to add medial cuneiform tenderness to the rules to minimize the chance of a missed fracture. Other authors have similarly suggested updates to the Ottawa Ankle Rules to improve overall yield.…”
Section: Discussionmentioning
confidence: 99%